Wavelength-Demultiplexed Laser Interferometry for Metrology - Zain Zaidi; Vala Fathipour; Xiangli Jia; Connie Chang-Hasnain (IEEE Photonics Journal, 2021)
Non-contact, cost-efficient, and long-range precision metrology is essential for applications in diverse areas, from 3D sensing and robotics to automated manufacturing, and multiwavelength interferometry is a compelling candidate. Here, we present a new arithmetic approach for multiwavelength phase unwrapping, with the maximum theoretical range and tolerance to measurement noise in phase. We supplement our formulation with a simultaneous phase shifting interferometry setup with a low measured standard deviation of phase, $σ _φ ={2π }/{1325}$ . We unwrap the interferometric phases of experiments performed through wavelengths with a greatest common divisor of 25 nm, demonstrate a range equal to their lowest-common-multiple with the precision of a single wavelength interferometer, and reconstruct three-dimensional scenes based on a single-pixel 3D imaging system.